Vicious Deep - Cordova, Zoraida (Naperville, Ill. : Sourcebooks Fire, 2012)
After being sucked out to sea in a tidal wave, Tristan Hart returns ashore on Coney Island with no memory of what happened to him--yet he can sense the emotions of others and dreams of a terrifying silver mermaid with razor-sharp teeth.
Keywords: Mermaids; Supernatural; Dreams; Fantasy; Paranormal fiction; Fantasy fiction